Pemetaan kerapatan bangunan pada tahun 2018 dan 2023 menggunakan Normalized Difference Built-Up Index (NDBI) di Kota Sukabumi - Muhammad, Deffry; Mataburu, Ilham Badaruddin (Jurnal Sains Geografi, 2024)
The growth of regional development activities in Indonesia has recently begun to grow very rapidly, especially in land use that has begun to be converted. Sukabumi city is one of the cities in Indonesia with continuous development. The NDBI method is a way to detect the index variable of built-up land. In 2018, it shows that the Sukabumi city area is dominated by non-built-up land, which is 3561.17 ha and the smallest is very dense settlements, which is 1.08 ha. In 2023, it is dominated by undeveloped land with an area of 3562.84 ha and the smallest area in very dense settlements with an area of about 0.3 ha only. undeveloped land has an additional land area of 0.02% or 1.67 ha. An increase also occurred in settlements with a sparse density of 1.12% or 28.43 ha. Settlements with a tight density have an inverse trend from the previous 2 classifications, decreasing by 44.78% or 29.34 ha. Then in settlements with very dense density, it has a downward trend of 57.06% or 0.78 ha. This is a fairly good trend, where there is an increase in undeveloped areas and a reduction in land with a tight and very tight density.